Preguntas y respuestas varias sobre la protección de datos personales en el Perú - Luna Cervantes, Eduardo Javier (2021)
This is intended to be an informative article. If desired, an approach to the issue of personal data protection in Peru, at the end of this decade that is concluding. I offer this from a free association of ideas that I connected as questions and answers, which came, if not, from my professional experience in the public function that I perform in the National Authority of Personal Data Protection of the Ministry of Justice and Human Rights; for sure, from the academic reflection that comes from my professional expertise. A curtain that opens a stage from which it is always more comfortable to write and self-identify.